High velocity nasal insufflation vs non-invasive positive pressure ventilation in the management of acute hypercapnic respiratory failure - Mohammed M. Elhofy; Ayman I. Baeis; Abdelmonaem M. Elshabrawy; Shaimaa Abdelghani Elbialy (Alexandria Journal of Medicine)
Introduction High-velocity nasal insufflation (HVNI) is a type of high-flow nasal cannula that depends on the dead-space clearance. HVNI utilizes small-bore nasal cannulae resulting in high velocity flow greater than the flow of the wider bore cannulae that were previously in use.Aim Assess the efficacy of high-velocity nasal insufflation in managing acute hypercapnic respiratory failure and compare between high-velocity nasal insufflations and noninvasive positive pressure ventilation (NIPPV) regarding efficacy and outcome in managing acute hypercapnic respiratory failure.Patients and Methods Over 12 months 48 patients admitted with a diagnosis of acute hypercapnic respiratory failure were enrolled in the study. Twenty-four patients were managed with HVNI, and the other 24 patients were managed with non-invasive ventilation. Patients were closely monitored in the respiratory intensive care unit (RICU). Oxygen saturation, respiratory rate, and Arterial Blood Gases (ABG) were measured before the start of treatment, then 1 hour, 4 hours, 2 days, and 3 days after treatment. Patients were allowed to crossover to the other arm of treatment or endotracheal intubation according to the clinical situation.Results pH, P Co2 levels showed similar changes in the two studied groups and improved with time. Treatment failure and mortality rates were also comparable in the two groups. Failure of treatment occurred in 16% in the group managed with HIVNI and in 33% in the group managed with NIPPV. Intubation at the end of 72 hourswas 16.7% in the group managed with HVNI and 25% in the group managed with NIPPV.Conclusion High velocity nasal insufflation is effective in managing acute hypercapnic respiratory failure. HVNI offers an effective way alternative to NIPPV in managing acute hypercapnic respiratory failure.